Study protocol of a pilot study on sirolimus-coated balloon angioplasty in salvaging clotted arteriovenous graft - Ru Yu Tan (CVIR Endovascular, 2020)
Abstract Background In arteriovenous graft (AVG) for haemodialysis, the primary cause of failure is venous stenosis of the graft-vein junction from neointimal hyperplasia (NIH), resulting in thrombosis. While interventions to salvage clotted AVG are known to have high clinical success rates, long-term patency rates have been suboptimal. Drug-coated balloon (DCB) has been used to treat stenosed arteriovenous access in recent years with encouraging results but data on its effect in clotted AVG is unavailable. Methods This is an investigator-initiated, single-center, single-arm prospective pilot study to determine the safety and outcome of the sirolimus-coated balloon (SCB) in the salvage of thrombosed AVG. Twenty patients who undergo successful percutaneous thrombectomy will receive treatment with SCB at the graft vein junction. The patients will be followed-up for 6-months. The primary endpoint is the patency rates at 3-month while the secondary endpoints are the patency rates and the number of interventions needed to maintain patency at 6-month. Discussion Unremitting efforts have been made to prolong the patency of AV accesses over the years. DCB angioplasty combines mechanical and biological treatment for vascular stenosis. Sirolimus, being a cystostatic anti-proliferative agent, has been successfully used in coronary artery interventions. As the primary pathology of vascular stenosis in the dialysis circuit is neointimal hyperplasia, the use of sirolimus in balloon angioplasty may be effective. With this prospective study, we evaluate the efficacy and safety of SCB in patients with clotted AVG. Trial registration ClinicalTrials.gov Identifier: NCT03666208 on 11 September 2018.